APLIKASI 17 LIVE VIDEO STREAMING MENJADI SARANA AKTUALISASI DIRI BAGI GENERASI MILLENIAL - Elly Komala (ArtComm, 2018)
The development of advanced technology helps a lot towards an increasingly practical, efficient and dynamic of life. Social media has also become the choice of many people to be a practical social media. For millennia, social media is a very important thing. Many are enabled to have social media accounts, as these generations are using more social media. Applications 17 Live is one of the live streaming applications that really help users to make streaming video capture and then directly watched by many people without the process of downloading. To express their own existence, millennial generations often use live streaming video applications to upload them with the aim of attracting people's attention through videos they upload and becoming famous. This application is also one means of self-actualization. Keywords: Applications 17 Live Video Streaming, Self Actualization, Millennial Generation